Preliminary Results on the Production of Heart of Coconut in Vanuatu. Effect of the Planting Density on the Yield - J. -P. Labouisse; T. Sileye; C. Hamelin; Xavier Bonneau; A. Rouzière (International Coconut Community, 2009)
This article presents the results of a field experiment on the production of heart of coconut (HOC) in Santo Island, Vanuatu. It demonstrated that the production of HOC is possible under the conditions of northern Vanuatu without irrigation and with low inputs. Only sodium chloride was applied as a fertiliser and the use of scrap copra sacks as a mulch was proved particularly efficient to reduce the weeds invasion and to preserve moisture. In this experiments, 3 densities of planting in an equilateral pattern with a spacing of 0.8 m, 1.4 m and 2.0 m were tested, and the growth parameters of the seedlings and the yield of the final product over a period of 2 years were recorded. It appeared that the higher the density of planting, the lower the weight of each HOC and the higher the yield by area unit. Two years after planting, the yield of HOC was 11.8 MT/hectare (0.8 m spacing), 7.7 MT/hectare (1.4 m) and 6.4 MT/hectare (2.0 m) with an average weight of HOC of 688 g, 1372 g and 2330 g respectively. The market requirement for HOC individual weight must be taken into account to choose the appropriate spacing and duration of cultivation. A strong relation between the stem girth and the HOC weight that can be described in the form of an allometric equation makes easy to estimate at any time the potential yield of HOC by measuring the stem girth of the whole palm.